Щодо питання захисту прав інтелектуальної власності - Токарева, Віра Олександрівна; Токарева, В. О.; Tokareva, Vira (ВД "Гельветика", 2020)
У статті проаналізований порядок захисту прав інтелектуальної власності, який здійснюється із застосуванням належних форм, засобів і способів захисту. Встановлено, що порушені права інтелектуальної власності можуть захищатися за допомогою норм різних галузей права та в порядку, встановленому адміністративним, цивільним і кримінальним законодавством. Разом з цим захист порушених авторських прав здійснюється переважно із застосуванням норм цивільного права.

The article analyzes issues for protecting intellectual property rights which is carried out using appropriate forms, means and methods of protection. It is established that intellectual property rights infringement may be protected in accordance with administrative, civil and criminal law. The protection of copyrights mainly is carried out with the application of civil law. The legal problems of protection of intellectual property rights are relevant, due to the increase of infringement of the intellectual property rights on the Internet and due to information and communication technologies using. In addition, Ukraine’s accession to the WTO has affected on the intensification of goods, services and intellectual property movement and thus the increase in the number of disputes. Intellectual property disputes may be related to infringement of the rights of authors and copyright holders, violation of rights. It is established that violation of intellectual property rights may occur due to non-compliance with the terms of the agreements on the disposal of intellectual property rights and non-contractual infringement of the rights to use the intellectual property objects. The violated intellectual property rights are subject of protection during the life of the authors and after their death. The Civil Code of Ukraine does not contain the definition of the concept of civil rights protection. Only Art. 15 provides the protection of civil rights and interests, which every person has the right to defend his civil right in the case of violation, non-recognition or contestation. Everyone has the right to the protection of his interests which is not contrary to the general principles of civil law. A prerequisite for the existence of a right is the ability to defend a violated right with the help of judicial or administrative authorities. In the absence of state protection, the right cannot exist, and in case of loss of the opportunity to protect the violated right, it is essentially terminated. The very likelihood of a person having a problem in the exercise of his right or in general termination of it in connection with the misconduct of third parties, leads to the need to protect the right.
Токарева, В. О. Щодо питання захисту прав інтелектуальної власності / В. О. Токарева / // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 51-56.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; право інтелектуальної власності; захист прав інтелектуальної власності; механізм захисту; форма захисту; способи захисту; intellectual property law; protection of intellectual property rights; form of protection; methods of protecting rights